Tratamento de incertezas no processamento de eventos complexos para internet das coisas através da teoria das evidências de dempster-shafer - BEZERRA, Eduardo Devidson Costa (2021)
The Internet of Things (IoT) has emerged from the proliferation of mobile devices and objects connected, so resulting in the acquisition of periodic event flows from different devices and sensors. However, such sensors and devices can be faulty or affected by failures, have poor calibration, producing in IoT applications inaccurate data and frequently unreliable event flows. In IoT, a prominent technique for analyzing event flows is Complex Event Processing (CEP). Uncertainty in event processing is usually observed in primitive events (i.e., sensor readings) and rules that derive complex events (i.e., high-level situations). In this study, we investigate the identification and treatment of uncertainty in CEP-based IoT applications. In this vein, we propose the DST-CEP, an approach that uses the Dempster-Shafer Theory to treat uncertainties. By using this theory, our solution can combine unreliable sensor data in conflicting situations and detect correct results. DST-CEP has an architectural model for treating uncertainty in events and its propagation to comlex event. Considering the proposed architectural model, a DST-CEP framework was implemented. We describe a case study using the proposed approach in a multi-sensor fire outbreak detection system. We submit our solution to experiments with a real sensor dataset, and evaluate it using well-known performance metrics. The solution achieves promising results regarding Accuracy, Precision, Recall, F-measure, and ROC Curve, even when combining conflicting sensor readings. DST-CEP demonstrates to be suitable and flexible to deal with questions of uncertainty raised in this research.